ARISE: A Phase 3 randomized trial of erenumab for episodic migraine - Dodick, David W; Ashina, Messoud; Brandes, Jan Lewis; Kudrow, David; Lanteri-Minet, Michel; Osipova, Vera; Palmer, Kerry; Picard, Hernan; Mikol, Daniel D; Lenz, Robert A (Cephalalgia, 2018)
Background Calcitonin gene-related peptide plays an important role in migraine pathophysiology. Erenumab, a human monoclonal antibody that inhibits the calcitonin gene-related peptide receptor, is being evaluated for migraine prevention. Methods In this randomized, double-blind, placebo-controlled, phase 3 study, 577 adults with episodic migraine were randomized to placebo or 70 mg erenumab; 570 patients were included in efficacy analyses. Primary endpoint was change in monthly migraine days. Secondary endpoints were ≥50% reduction in monthly migraine days, change in acute migraine-specific medication treatment days, and ≥5-point reduction in Physical Impairment and Impact on Everyday Activities domain scores measured by the Migraine Physical Function Impact Diary. All endpoints assessed change from baseline at month 3. Results Patients receiving erenumab experienced −2.9 days change in monthly migraine days, compared with −1.8 days for placebo, least-squares mean (95% CI) treatment difference of −1.0 (−1.6, −0.5) (p < 0.001). A ≥ 50% reduction in monthly migraine days was achieved by 39.7% (erenumab) and 29.5% (placebo) of patients (OR:1.59 (95% CI: 1.12, 2.27) (p = 0.010). Migraine-specific medication treatment days were reduced by −1.2 (erenumab) and −0.6 (placebo) days, a treatment difference of −0.6 (−1.0, −0.2) (p = 0.002). The ≥5-point reduction rates in Migraine Physical Function Impact Diary – Physical Impairment were 33.0% and 27.1% (OR:1.33 (0.92, 1.90) (p = 0.13) and in Migraine Physical Function Impact Diary – Everyday Activities were 40.4% and 35.8% (OR:1.22 (0.87, 1.71) (p = 0.26). Safety and adverse event profiles of erenumab were similar to placebo. Most frequent adverse events were upper respiratory tract infection, injection site pain, and nasopharyngitis. Conclusions As a preventive treatment of episodic migraine, erenumab at a dosage of 70 mg monthly significantly reduced migraine frequency and acute migraine-specific medication use. (Funded by Amgen). Trial registration ClinicalTrials.gov, NCT02483585.